When the Creation of a Consortium Provides Useful Answers: Experience of The Latin American DILI Network (LATINDILIN). Issue 2 (4th March 2019) - Bessone, Fernando; Hernandez, Nelia; Mendizabal, Manuel; Sanchez, Adriana; Paraná, Raymundo; Arrese, Marco; Tagle, Martin; Girala, Marcos; Lizarzabal, Maribel; Carrera, Enrique; Brahm, Javier; Contreras, Fernando; et al.
Abstract : Watch a video presentation of this article Watch the interview with the author (English) Watch the interview with the author (Spanish)